Functional Properties of Collagen from Purple-spotted Bigeye (Priacanthus tayenus Richardson, 1846) Bone and Fins Extracted with Different Acids - Hajariah Hasanuddin; Abdul Aziz Jaziri; Rossita Shapawi; Ruzaidi Azli Mohd Mokhtar; Wan Norhana Md. Noordin; Frederick Adzitey; Nurul Huda (IJASEIT, 2023)
This work aimed to evaluate the functional properties of collagen derived from the bone and fins of Priacanthus tayenus (Richardson, 1846) prepared with various organic acids. The extracted collagens yielded 0.83%, 1.43%, and 1.93% of acetic acid-extracted collagen (AEC), lactic acid-extracted collagen (LEC), and citric acid-extracted collagen (CEC), respectively, although no significant differences (p > 0.05). The high solubility was detected in all extracted collagen samples under low concentrations of sodium chloride (up to 20 g/L). Acetic and lactic acid-extracted collagens showed the highest solubility at pH 3 and pH 5 for citric acid-extracted collagen. The oil absorption capacity varied from 8.57 mL/mg to 15.94 mL/mg and was significantly the highest (p < 0.05) for the AEC sample. Although the highest water absorption capacity was noted in LEC (14.39 mL/mg) compared to AEC (12.44 mL/mg) and CEC (8.30 mL/mg), it is not significantly different (p > 0.05). All the extracted samples recorded higher values of foaming ability (from 78.33% to 88.33%) and stability (from 80% to 93.33%) at pH 4. Therefore, the emulsion characteristics comprising the emulsion ability and stability indexes were carried out under acidic pH conditions, and the results showed acetic-extracted collagen had the highest values compared to lactic and citric acid-extracted collagens. Taken together, P. tayenus collagens had good functional properties comparable to other collagen sources, supporting its further use in industrial processes.